2018
DOI: 10.1186/s13569-018-0105-y
|View full text |Cite
|
Sign up to set email alerts
|

Periostin expression in neoplastic and non-neoplastic diseases of bone and joint

Abstract: BackgroundPeriostin is a matricellular protein that is expressed in bone and joint tissues. To determine the expression of periostin in primary bone tumours and to assess whether it plays a role in tumour progression, we carried out immunohistochemistry and ELISA for periostin in a range of neoplastic and non-neoplastic bone and joint lesions.Methods140 formalin-fixed paraffin-embedded sections of bone tumours and tumour-like lesions were stained by an indirect immunoperoxidase technique with a polyclonal anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Similar lowercase letter (a) indicates statistical significance between groups at P < 0.05. correlated with the severity and the risk of progression of knee OA 24,25,35 . One contrasting study reported higher levels of POSTN in the synovial fluid of RA patients than in OA patients 36 . Cartilage from human and mouse OA knees has been shown to exhibit higher expression of POSTN than normal cartilage 12,23 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Similar lowercase letter (a) indicates statistical significance between groups at P < 0.05. correlated with the severity and the risk of progression of knee OA 24,25,35 . One contrasting study reported higher levels of POSTN in the synovial fluid of RA patients than in OA patients 36 . Cartilage from human and mouse OA knees has been shown to exhibit higher expression of POSTN than normal cartilage 12,23 .…”
Section: Discussionmentioning
confidence: 96%
“…The complete source of POSTN in the joint is not known although it is thought that many tissues in the joint express and produce POSTN such as bone 18 , cartilage 12,23,34 , ACL 12,15 , meniscus 40 and synovium 36 . However, to date, no quantitative comparison of POSTN expression between various joint tissues has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…RA is a chronic inflammatory disease affecting the joints caused by autoantibodies. Periostin has been shown to be upregulated in cells of the synovium and the synovial fluid in RA (17,18). In cultured human chondrocytes, periostin induces the expression of IL-6, IL-8, MMP-1, MMP-3 and MMP13, which could be linked to the development of the disease (19).…”
Section: Rheumatoid Arthritis (Ra) and Ankylosing Spondylitis (As)mentioning
confidence: 99%
“…Interestingly, periostin was found to be mainly localized in tumor cells in osteosarcoma tissues, and correlated with vessel density (31). Scanty data are instead available on its detection in STS (32). Our results clearly show for the first time that this multifunctional protein may be overexpressed in tissue samples of the three studied subtypes.…”
Section: Discussionmentioning
confidence: 60%